An exploration of business model development in the commercialization of technology innovations. (June 2014) - Dmitriev, Viatcheslav; Simmons, Geoff; Truong, Yann; Palmer, Mark; Schneckenberg, Dirk; Spieth, Patrick; Schneckenberg, Dirk; Ricart, Joan E.
<x xml:space="preserve">Abstract</x> Research on business model development has focused on the relationships between elements of value conceptualization and organization having a linear sequence in which business models are first designed and then implemented. Another stream of research points to business model development with these elements interacting in a cyclical manner. There is a need to improve our understanding of the connective mechanisms and dynamics involved in business model development, particularly from the challenging perspective of commercializing innovations. The aim of this paper was to explore business model development during the commercialization of innovations through a case‐based qualitative study. This study found from four case studies that specific elements of business model development, representative of the conceptualization of value and organizing for value creation, integrate in a dynamic and cyclical process in the commercialization of technology innovations. The study provides empirical evidence that adds new insights to literature on sequential and more interactive processes of business model development. It also contributes to literature on business model development and particularly how it relates to the commercialization of innovations.